Meningkatkan Kemampuan Menulis Teks Argumentatif dalam Bahasa Inggris melalui Collaborative Learning - Dyah Laila Safriani; Siti Aimah; Rulik Dwiyamtini (Journal of Lesson Study in Teacher Education, 2024)
This study aims to improve the argumentative text writing skills of Grade XII B3 students at SMA Negeri 15 Semarang through Collaborative Learning using the Jigsaw model and Peer Feedback. The research adopts a Classroom Action Research (CAR) approach. The subjects of the study were 33 regular students in the first semester of the 2024/2025 academic year. The results indicate a significant improvement in students' writing skills. The initial average score was 60.9, with a mastery level of 39.39% (13 students achieving mastery). After the first cycle, the average score increased to 79.8, with a mastery level of 63.63% (21 students achieving mastery). By the second cycle, the average score reached 84.8, with a mastery level of 78.79% (26 students achieving mastery). These improvements reflect the effectiveness of the Jigsaw model in fostering collaboration and the role of Peer Feedback in providing constructive responses. The findings suggest that collaborative learning enhances critical thinking, self-confidence, and writing skills among students. This model also strengthens interactions among students through group collaboration and intensive discussions. The study recommends the application of Collaborative Learning models in other subjects to promote the development of 21st-century skills, such as critical thinking, communication, collaboration, and creativity.